Neue Möglichkeiten zur Nutzung vertraulicher amtlicher Personen- und Firmendaten - Ulrich Kaiser; Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2007)
Researchers in Germany have nowadays access to confidential micro data compiled from official statistics in a way that could not have been dreamt of just a few years ago. This paper describes the new institutions that grant data access - most importantly the research data centers located inside the data producing agencies - and how to access the micro data, and presents information about selected recently released data sets with a high potential for scientific research and policy evaluation...
Keywords: 330; Mikrodaten; Statistische Methode; Wirtschaftsforschung; Deutschland